Method for electrochemical sodium supplementation, layered sodium-ion positive electrode material and battery

CN117954715BActive Publication Date: 2026-10-09SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410136287.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2026-10-09
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

但是,该钠离子电池补钠的方法需要补充新的钠的氧化物,从而导致成本较高

Benefits of technology

[0059] The electrochemical sodium replenishment method provided by this invention replenishes sodium in air-depleted layered sodium ion transition metal oxide cathode materials to obtain layered sodium ion cathode materials. Sodium-ion batteries prepared with the layered sodium ion cathode materials have high initial capacity and excellent cycle stability. In addition, the method also has the advantages of simple technical route and low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117954715B_ABST
    Figure CN117954715B_ABST
Patent Text Reader

Abstract

The application provides a method for electrochemical sodium supplement, a layered sodium ion positive electrode material and a battery. The method comprises the following steps: preparing a battery by taking an air failure layered sodium ion transition metal oxide positive electrode material as a positive electrode material; discharging the obtained battery to a first voltage at a first current density; charging the battery to a second voltage at a second current density; and then performing activation at a third current density in a set voltage interval to obtain a layered sodium ion positive electrode material. The method for electrochemical sodium supplement provided by the application obtains a layered sodium ion positive electrode material after supplementing sodium to an air failure layered sodium ion transition metal oxide positive electrode material. A sodium ion battery prepared from the layered sodium ion positive electrode material has a high initial capacity and excellent cycle stability. In addition, the method also has the advantages of a simple technical route and low production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, relates to an electrochemical sodium supplementation method, and particularly relates to an electrochemical sodium supplementation method, a layered sodium-ion cathode material and a battery. Background Art

[0002] Since commercialization by Sony Corporation in 1991, lithium-ion batteries have achieved great success in applications such as portable electronic products, electric vehicles and smart grids. However, the characteristics of scarce lithium resources and uneven distribution in nature make the cost of lithium-ion batteries increase year by year. Meanwhile, the sustainable development of lithium resources has also become a focus of attention. Sodium has similar physical and chemical properties to lithium, and in addition, sodium has the characteristics of abundant resources, uniform distribution and low extraction cost. Therefore, sodium-ion batteries are regarded as a beneficial supplement to lithium-ion batteries, and have shown broad application prospects in the field of large-scale energy storage in recent years.

[0003] Since layered sodium-ion transition metal oxide cathode material (Na x TMO2, 0<x≤1) has the advantages of high specific capacity, simple preparation process, adjustable voltage and low cost, it has received extensive attention and research in academia and industry, and the material has been demonstrated and verified in a 100kW·h-class sodium-ion battery energy storage power station. However, currently, layered Na x TMO2 cathode material still has the disadvantage of air sensitivity. Once exposed to air, sodium in the bulk phase of the material will lose to the surface, and undergo unfavorable side reactions with H2O / CO2 in air, eventually leading to strong distortion of the crystal structure and rapid capacity attenuation. In actual industrial production, it is necessary to use a dry or inert atmosphere to effectively isolate the layered Na x TMO2 cathode material from air, so as to avoid air failure of the layered Na x TMO2 cathode material during manufacturing, transportation and storage, which leads to a substantial increase in cost. It can be seen that air sensitivity is one of the main obstacles to realizing commercial application of high-performance, high-safety and low-cost layered Na x TMO2 cathode material.

[0004] In view of the above problems, researchers have also proposed corresponding solutions, such as high-temperature calcination, element doping and surface coating. However, these methods all have the disadvantages of complex technical routes and high production costs, and are not suitable for large-scale production. In view of this, it is extremely urgent to use a simple electrochemical sodium supplementation method to solve the problems of structural damage and capacity loss caused by air exposure of layered Na x TMO2 cathode material while controlling the cost.

[0005] CN106848453A discloses a method for replenishing sodium in a sodium-ion battery, comprising: mixing a metallic element with a sodium salt in a certain molar ratio and adding it as a positive electrode additive to the positive electrode active material to prepare a sodium-ion battery positive electrode sheet, and assembling it into a battery; during the battery formation stage, controlling the initial charging voltage range to allow the metallic element and sodium salt to react completely, releasing sodium ions from the positive electrode additive to the negative electrode sheet to participate in the formation of the SEI film; controlling the battery cycle charge and discharge voltage range to allow the sodium-ion battery to enter the normal charge and discharge state, with the metallic element in the additive existing in the battery in the form of a metal compound. However, the performance of the sodium-ion battery positive electrode material obtained after replenishing sodium using this method is still insufficient.

[0006] CN111293289A discloses a method for replenishing sodium in a sodium-ion battery, comprising: mixing sodium oxide with a positive electrode active material in a certain molar ratio and ball milling to obtain a mixed positive electrode active material; using this material to prepare a sodium-ion battery positive electrode sheet and assembling it into a battery; during the battery formation stage, controlling the initial charge and discharge voltage range to ensure that the sodium oxide reacts completely and releases all sodium ions to the negative electrode sheet to participate in the formation of the SEI film; and controlling the battery usage conditions to bring the battery into normal operating condition. However, this method for replenishing sodium in a sodium-ion battery requires the addition of new sodium oxide, resulting in high costs.

[0007] Currently available electrochemical methods for sodium replenishment all have certain drawbacks, including their inability to effectively address layered Na+ formations. x The failure of TMO2 cathode materials in air leads to structural damage and capacity loss, as well as the complexity and high production cost of the technical route. Therefore, it is crucial to develop a novel electrochemical sodium replenishment method, layered sodium-ion cathode materials, and batteries. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the present invention aims to provide an electrochemical sodium replenishment method, a layered sodium-ion cathode material, and a battery. The electrochemical sodium replenishment method provided by the present invention replenishes sodium in an air-depleted layered sodium-ion transition metal oxide cathode material to obtain a layered sodium-ion cathode material. Sodium-ion batteries prepared with the layered sodium-ion cathode material exhibit high initial capacity and excellent cycle stability. In addition, the method also has the advantages of simple technical route and low production cost.

[0009] To achieve this objective, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a method for electrochemical sodium supplementation, the method comprising:

[0011] A battery is prepared using air-depleted layered sodium ion transition metal oxide cathode material as the cathode material. The resulting battery is discharged to a first voltage at a first current density, then charged to a second voltage at a second current density, and then activated at a third current density within a set voltage range to obtain the layered sodium ion cathode material.

[0012] The electrochemical sodium replenishment method provided by this invention replenishes sodium in air-depleted layered sodium ion transition metal oxide cathode materials to obtain layered sodium ion cathode materials. Sodium-ion batteries prepared with the layered sodium ion cathode materials have high initial capacity and excellent cycle stability. In addition, the method also has the advantages of simple technical route and low production cost.

[0013] Preferably, the first current density is 10 to 50 mA / g, for example, it can be 10 mA / g, 15 mA / g, 20 mA / g, 25 mA / g, 30 mA / g, 35 mA / g, 40 mA / g, 45 mA / g or 50 mA / g, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0014] Preferably, the second current density is 10 to 50 mA / g, for example, it can be 10 mA / g, 15 mA / g, 20 mA / g, 25 mA / g, 30 mA / g, 35 mA / g, 40 mA / g, 45 mA / g or 50 mA / g, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0015] Preferably, the third current density is 10 to 50 mA / g, for example, it can be 10 mA / g, 15 mA / g, 20 mA / g, 25 mA / g, 30 mA / g, 35 mA / g, 40 mA / g, 45 mA / g or 50 mA / g, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0016] Preferably, the first voltage is 0.5 to 2V, for example, it can be 0.5V, 0.6V, 0.7V, 0.8V, 0.9V, 1V, 1.1V, 1.2V, 1.3V, 1.4V, 1.5V, 1.6V, 1.7V, 1.8V, 1.9V or 2V, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0017] Preferably, the second voltage is 4 to 4.4V, for example, it can be 4V, 4.05V, 4.1V, 4.2V, 4.25V, 4.3V, 4.35V or 4.4V, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0018] Preferably, the lowest voltage in the set voltage range is 1.5 to 2.5V, and the highest voltage is 4 to 5V.

[0019] The lowest voltage in the voltage range specified in this invention is 1.5 to 2.5V, for example, it can be 1.5V, 1.6V, 1.7V, 1.8V, 1.9V, 2V, 2.1V, 2.2V, 2.3V, 2.4V or 2.5V, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0020] The highest voltage in the voltage range specified in this invention is 4 to 5V, for example, it can be 4V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, 4.6V, 4.7V, 4.8V, 4.9V or 5V, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0021] Preferably, the number of activation cycles is 3 to 5, for example, 3, 4 or 5 cycles.

[0022] Preferably, the method for preparing the battery includes:

[0023] A slurry is obtained by mixing a positive electrode adhesive, a conductive agent, and an air-defective layered sodium ion transition metal oxide positive electrode material. The slurry is then coated onto a current collector and rolled to obtain a positive electrode sheet. The positive electrode sheet is then combined with a negative electrode sheet, a separator, and an electrolyte to form a battery.

[0024] Preferably, the preparation of the positive electrode adhesive includes: premixing the binder and solvent in a dry environment with a dew point temperature below -40 to -60°C to obtain the positive electrode adhesive.

[0025] In this invention, premixing is carried out in a dry environment with a dew point temperature below -40 to -60°C. For example, the temperature can be -40°C, -42°C, -45°C, -47°C, -50°C, -52°C, -55°C, -57°C, or -60°C, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0026] Preferably, the premixing method includes stirring for 5 to 15 hours.

[0027] Preferably, the mass ratio of binder to solvent in the positive electrode adhesive is 1:(20-30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0028] Preferably, the adhesive comprises any one or a combination of at least two of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile polymers, polyimide polymers, or perfluorosulfonic acid ionomers. Typical but non-limiting combinations include combinations of polyvinylidene fluoride and polyacrylic acid, combinations of polyacrylic acid and polyacrylonitrile polymers, combinations of polyacrylonitrile polymers and polyimide polymers, combinations of polyimide polymers and perfluorosulfonic acid ionomers, or combinations of polyvinylidene fluoride, polyacrylic acid, and polyacrylonitrile polymers.

[0029] Preferably, the solvent comprises any one or a combination of at least two of N-methylpyrrolidone, dimethylformamide, dimethyl sulfoxide, or dihydro-L-glucoside. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and dimethylformamide, a combination of dimethyl sulfoxide and dihydro-L-glucoside, or a combination of N-methylpyrrolidone, dimethylformamide, and dimethyl sulfoxide.

[0030] Preferably, the conductive agent includes any one or a combination of at least two of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes or graphene, a combination of conductive carbon black and conductive graphite, a combination of conductive graphite and carbon fiber, a combination of carbon nanotubes and graphene, or a combination of conductive carbon black, conductive graphite and carbon fiber.

[0031] Preferably, the air-defect layered sodium-ion transition metal oxide cathode material comprises air-defect layered NaxTMO2, wherein TM comprises any one or at least two combinations of Ni, Fe, Mn or Co. Typical but non-limiting combinations include combinations of Ni and Fe, Fe and Mn, Mn and Co, or Ni, Fe and Mn.

[0032] Preferably, the air-depleted layered NaxTMO2 comprises layered oxides of type O3 or P2.

[0033] Preferably, the mixing method includes stirring for 10 to 20 hours in a dry environment with a dew point temperature below -40 to -60°C.

[0034] In this invention, mixing is carried out in a dry environment with a dew point temperature below -40 to -60°C, for example, -40°C, -42°C, -45°C, -47°C, -50°C, -52°C, -55°C, -57°C or -60°C, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0035] The mixing time described in this invention is 10 to 20 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0036] Preferably, the mass ratio of the positive electrode adhesive, conductive agent and air-depleted layered sodium ion transition metal oxide positive electrode material in the mixture is (0.5-1.5):(0.5-1.5):8.

[0037] The mass ratio of the positive electrode adhesive and the air-depleted layered sodium ion transition metal oxide positive electrode material in the mixture described in this invention is, for example, (20-30):8, such as 20:8, 21:8, 22:8, 23:8, 24:8, 25:8, 26:8, 27:8 or 28:8, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0038] 0.5:8, 0.6:8, 0.7:8, 0.8:8, 0.9:8, 1:8, 1.1:8, 1.2:8, 1.3:8, 1.4:8 or 1.5:8, but not limited to the listed values; other unlisted values ​​within this range also apply.

[0039] The mass ratio of the conductive agent to the air-depleted layered sodium ion transition metal oxide cathode material in the mixture described in this invention is, for example, (0.5 to 1.5):8, such as 0.5:8, 0.6:8, 0.7:8, 0.8:8, 0.9:8, 1:8, 1.1:8, 1.2:8, 1.3:8, 1.4:8, or 1.5:8, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0040] Preferably, the preparation method further includes drying the air-defective layered sodium ion transition metal oxide cathode material before mixing.

[0041] Preferably, the drying temperature is 105-150°C and the drying time is 20-30 hours.

[0042] The drying temperature described in this invention is 105 to 150°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0043] The drying time described in this invention is 20 to 30 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0044] Preferably, the preparation method further includes drying between the coating and the rolling process.

[0045] Preferably, the drying temperature is 105–150°C and the drying time is 5–30 hours.

[0046] The drying temperature described in this invention is 105 to 150°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0047] The drying time described in this invention is 5 to 30 hours, for example, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 25 hours, 28 hours or 30 hours, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0048] Preferably, the pressure of the roller is 5 to 15 MPa, for example, it can be 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa or 15 MPa, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0049] Preferably, the compacted density after roller pressing is 1–3 g / cm³. 3 For example, it could be 1g / cm 3 1.2g / cm 3 1.4g / cm 3 1.6g / cm 3 1.8g / cm 3 2g / cm 3 2.2g / cm 3 2.4g / cm 3 2.6g / cm 3 2.8g / cm 3 Or 3g / cm 3 However, this does not apply to all values ​​listed; other unlisted values ​​within the same range also apply.

[0050] Preferably, the areal density of the positive electrode sheet is 5.5–6 mg / cm³. 2For example, it could be 5.5 mg / cm³ 2 5.55 mg / cm 2 5.6 mg / cm 2 5.65 mg / cm 2 5.7 mg / cm 2 5.75 mg / cm 2 5.8 mg / cm 2 5.85 mg / cm 2 5.9 mg / cm 2 5.95 mg / cm 2 Or 6mg / cm 2 However, this does not apply to all values ​​listed; other unlisted values ​​within the same range also apply.

[0051] Preferably, the negative electrode sheet comprises a sodium sheet and / or hard carbon.

[0052] Preferably, the diaphragm includes any one or a combination of at least two of glass fiber diaphragms, polyethylene diaphragms, or polypropylene diaphragms. Typical but non-limiting combinations include a combination of glass fiber diaphragms and polyethylene diaphragms, a combination of polyethylene diaphragms and polypropylene diaphragms, or a combination of glass fiber diaphragms, polyethylene diaphragms, and polypropylene diaphragms.

[0053] The glass fiber diaphragm described in this invention includes Grade GF / A or Grade GF / D. When the glass fiber diaphragm is Grade GF / A, the amount of electrolyte is 100 μl; when the glass fiber diaphragm is Grade GF / D, the amount of electrolyte is 150 μl.

[0054] Preferably, the electrolyte includes any one or a combination of at least two of NaClO4 electrolyte, NaPF6 electrolyte, NaTFSI electrolyte, or NaFSI electrolyte. Typical but non-limiting combinations include a combination of NaClO4 electrolyte and NaPF6 electrolyte, a combination of NaTFSI electrolyte and NaFSI electrolyte, or a combination of NaClO4 electrolyte, NaPF6 electrolyte, and NaTFSI electrolyte.

[0055] The NaClO4 electrolyte described in this invention contains dimethyl carbonate and fluoroethylene carbonate.

[0056] In a second aspect, the present invention provides a layered sodium ion cathode material, wherein the layered sodium ion transition metal oxide cathode material is obtained by the method described in the first aspect.

[0057] Thirdly, the present invention provides a battery comprising the layered sodium-ion transition metal oxide cathode material described in the second aspect.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The electrochemical sodium replenishment method provided by this invention replenishes sodium in air-depleted layered sodium ion transition metal oxide cathode materials to obtain layered sodium ion cathode materials. Sodium-ion batteries prepared with the layered sodium ion cathode materials have high initial capacity and excellent cycle stability. In addition, the method also has the advantages of simple technical route and low production cost. Attached Figure Description

[0060] Figure 1 The layered Na in Embodiment 1 of the present invention 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Low-magnification SEM image of O2.

[0061] Figure 2 The layered Na of type P2 obtained after air storage for 7 days as described in Example 1 of this invention. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Low-magnification SEM image of O2.

[0062] Figure 3 The layered Na in Embodiment 1 of the present invention 0.75 Ni 0.2 Fe 0.4 Mn 0.4 High-magnification SEM image of O2.

[0063] Figure 4 The layered Na of type P2 obtained after air storage for 7 days as described in Example 1 of this invention. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 High-magnification SEM image of O2.

[0064] Figure 5 The layered Na of the present invention 0.75 Ni 0.2 Fe 0.4 Mn 0.4 XRD pattern of O2.

[0065] Figure 6 The image shows the XRD pattern of the layered sodium ion cathode material obtained by the electrochemical sodium supplementation method in Example 1 of this invention.

[0066] Figure 7 This is the first-cycle capacity-voltage curve of a battery containing layered sodium ion cathode material obtained by the electrochemical sodium supplementation method in Example 1 of the present invention.

[0067] Figure 8 To use the layered Na in Embodiment 1 of the present invention 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Layered Na of type P2 obtained after storage in O2 and air for 7 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Cycle performance diagram of batteries prepared with O2 and layered sodium ion cathode materials. Detailed Implementation

[0068] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0069] Example 1

[0070] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0071] (1) In a dry environment with a dew point temperature below -50℃, polyvinylidene fluoride and N-methylpyrrolidone were premixed with stirring for 10 hours at a mass ratio of 1:24 to obtain a positive electrode solution.

[0072] (2) The layered Na shown 0.75 Ni 0.2 Fe 0.4 Mn 0.4 P2-type air-depleted layered Na obtained after O2 is stored in air for 7 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was dried at 105℃ for 24 hours to obtain the dried cathode material;

[0073] (3) The positive electrode solution obtained in step (1) with a mass ratio of (20~30):1:8, conductive carbon black and the dried positive electrode material obtained in step (3) are stirred and mixed for 10 hours in a dry environment with a dew point temperature below -50℃ to obtain a slurry.

[0074] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 105℃ for 5 hours, and then press it with a pressure roller at 10MPa to obtain a compaction density of 3g / cm³. 3 The positive electrode sheet was obtained and then combined with sodium sheet, glass fiber separator Grade GF / A and NaClO4 electrolyte to prepare CR2032 button cell.

[0075] (5) The obtained CR2032 button cell was discharged to 1.8V at a current density of 10mA / g, and then charged to 4.2V at a current density of 10mA / g. After activation for 3 cycles at a current density of 10mA / g within the set voltage range of 2 to 4.4V, a cell containing layered sodium ion positive electrode material was obtained. After peeling, the layered sodium ion positive electrode material was obtained.

[0076] The layered Na in step (2) was examined using a scanning electron microscope. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Layered Na of type P2 obtained after 7 days of storage in O2 and air. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was used for testing, and layered Na was obtained. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 SEM image of O2 at low magnification: Figure 1 As shown, the SEM image at high magnification is as follows: Figure 3 As shown, layered Na of type P2 obtained after 7 days of air storage. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 SEM image of O2 at low magnification: Figure 2 As shown, the SEM image at high magnification is as follows: Figure 4 As shown;

[0077] The layered Na in step (2) was analyzed using an XRD diffractometer. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Layered Na of type P2 obtained after 7 days of storage in O2 and air. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was used for testing, and layered Na was obtained. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 The XRD pattern of O2 is as follows: Figure 5 As shown, layered Na of type P2 obtained after 7 days of air storage. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 The XRD pattern of O2 is as follows: Figure 6 As shown.

[0078] Example 2

[0079] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0080] (1) In a dry environment with a dew point temperature below -50℃, a positive electrode solution was obtained by stirring and premixing polyvinylidene fluoride and N-methylpyrrolidone at a mass ratio of 1:24 for 10 hours.

[0081] (2) Layered Na 0.75 Ni 0.2 Fe 0.4 Mn 0.4 P2-type air-depleted layered Na obtained after O2 is stored in air for 14 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was dried at 105℃ for 24 hours to obtain the dried cathode material;

[0082] (3) The positive electrode solution obtained in step (1) with a mass ratio of 25:1:8, conductive carbon black and the dried positive electrode material obtained in step (3) are stirred and mixed for 10 hours in a dry environment with a dew point temperature below -50℃ to obtain a slurry.

[0083] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 105℃ for 5 hours, and then press it with a pressure roller at 10MPa to obtain a compaction density of 3g / cm³. 3 The positive electrode sheet was obtained and then combined with sodium sheet, glass fiber separator Grade GF / A and NaClO4 electrolyte to prepare CR2032 button cell.

[0084] (5) The obtained CR2032 button cell was discharged to 1.3V at a current density of 10mA / g, and then charged to 4.2V at a current density of 10mA / g. After activation for 3 cycles at a current density of 10mA / g within the set voltage range of 2 to 4.4V, a cell containing layered sodium ion positive electrode material was obtained. After peeling, the layered sodium ion positive electrode material was obtained.

[0085] Example 3

[0086] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0087] (1) In a dry environment with a dew point temperature below -50℃, a positive electrode solution was obtained by stirring and premixing polyvinylidene fluoride and N-methylpyrrolidone at a mass ratio of 1:24 for 10 hours.

[0088] (2) Layered Na 0.75 Ni 0.2 Fe 0.4 Mn 0.4P2-type air-depleted layered Na obtained after O2 is stored in air for 7 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was dried at 105℃ for 24 hours to obtain the dried cathode material;

[0089] (3) The positive electrode solution obtained in step (1) with a mass ratio of 25:1:8, conductive carbon black and the dried positive electrode material obtained in step (3) are stirred and mixed for 10 hours in a dry environment with a dew point temperature below -50℃ to obtain a slurry.

[0090] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 105℃ for 5 hours, and then press it with a pressure roller at 10MPa to obtain a compaction density of 3g / cm³. 3 The positive electrode sheet was obtained and then combined with sodium sheet, glass fiber separator Grade GF / A and NaClO4 electrolyte to prepare CR2032 button cell.

[0091] (5) The obtained CR2032 button cell was discharged to 1.8V at a current density of 10mA / g, and then charged to 4.2V at a current density of 10mA / g. After activation for 3 cycles at a current density of 10mA / g within the set voltage range of 2 to 4.2V, a cell containing layered sodium ion positive electrode material was obtained. After peeling, the layered sodium ion positive electrode material was obtained.

[0092] Example 4

[0093] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0094] (1) In a dry environment with a dew point temperature below -50℃, a positive electrode solution was obtained by stirring and premixing polyvinylidene fluoride and N-methylpyrrolidone at a mass ratio of 1:24 for 10 hours.

[0095] (2) Layered Na 0.75 Ni 0.2 Fe 0.4 Mn 0.4 P2-type air-depleted layered Na obtained after O2 is stored in air for 14 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 O2 was dried at 105℃ for 24 hours to obtain the dried cathode material;

[0096] (3) The positive electrode solution obtained in step (1) with a mass ratio of 25:1:8, conductive carbon black and the dried positive electrode material obtained in step (3) are stirred and mixed for 10 hours in a dry environment with a dew point temperature below -50℃ to obtain a slurry.

[0097] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 105℃ for 5 hours, and then press it with a pressure roller at 10MPa to obtain a compaction density of 3g / cm³. 3 The positive electrode sheet was obtained and then combined with sodium sheet, glass fiber separator Grade GF / A and NaClO4 electrolyte to prepare CR2032 button cell.

[0098] (5) The obtained CR2032 button cell was discharged to 1.3V at a current density of 10mA / g, and then charged to 4.2V at a current density of 10mA / g. After activation for 3 cycles at a current density of 10mA / g within the set voltage range of 2 to 4.2V, a cell containing layered sodium ion positive electrode material was obtained. After peeling, the layered sodium ion positive electrode material was obtained.

[0099] Example 5

[0100] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0101] (1) In a dry environment with a dew point temperature below -40°C, a positive electrode solution was obtained by stirring and premixing polyacrylic acid and dimethylformamide at a mass ratio of 1:30 for 5 hours.

[0102] (2) The layered Na3MnO2 obtained by air storage for 7 days was dried at 105°C for 30 hours to obtain the dried cathode material.

[0103] (3) The positive electrode solution obtained in step (1) with a mass ratio of 30:1.5:8, carbon fiber and the dried positive electrode material obtained in step (3) are stirred and mixed for 10 hours in a dry environment with a dew point temperature below -40℃ to obtain a slurry.

[0104] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 150°C for 5 hours, and then press it with a pressure roller at 5 MPa to obtain a compaction density of 1 g / cm³. 3 The positive electrode sheet is obtained and then combined with hard carbon, polyethylene separator and NaPF6 electrolyte to prepare a battery.

[0105] (5) Discharge the obtained battery to 0.5V at a current density of 50mA / g, then charge it to 4V at a current density of 50mA / g, and then activate it for 3 cycles at a current density of 10mA / g within a set voltage range of 2.5 to 5V to obtain a battery containing layered sodium ion positive electrode material. After peeling, the layered sodium ion positive electrode material is obtained.

[0106] Example 6

[0107] This embodiment provides a method for electrochemical sodium supplementation, the method comprising:

[0108] (1) In a dry environment with a dew point temperature below -60°C, a positive electrode solution was obtained by stirring and premixing polyacrylic acid and dimethyl sulfoxide at a mass ratio of 1:20 for 15 hours.

[0109] (2) Layered Na 0.44 The O3-type air-depleted layered Na obtained after MnO2 is stored in air for 7 days 0.44 MnO2 was dried at 150℃ for 20 hours to obtain the dried cathode material;

[0110] (3) The positive electrode solution obtained in step (1) with a mass ratio of 20:0.5:8, carbon nanotubes and the dried positive electrode material obtained in step (3) are stirred and mixed for 20 hours in a dry environment with a dew point temperature below -60℃ to obtain a slurry.

[0111] (4) After coating the slurry obtained in step (3) onto the current collector, dry it at 105°C for 30 hours, and then press it with a pressure roller at 15 MPa to obtain a compaction density of 2 mg / cm³. 2 The positive electrode sheet is obtained and then combined with sodium sheet, polypropylene membrane and NaTFSI electrolyte to prepare a battery.

[0112] (5) Discharge the obtained battery to 2V at a current density of 10mA / g, then charge it to 4.4V at a current density of 10mA / g, and then activate it for 5 cycles at a current density of 50mA / g within a set voltage range of 1.5 to 4V to obtain a battery containing layered sodium ion positive electrode material. After peeling, the layered sodium ion positive electrode material is obtained.

[0113] Example 7

[0114] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that the discharge is performed at a current density of 5 mA / g in step (5).

[0115] Example 8

[0116] This embodiment provides a method for electrochemical sodium replenishment. Except for the discharge at a current density of 70 mA / g in step (5), the rest is the same as in Example 1.

[0117] Example 9

[0118] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that in step (5) the sodium is discharged to 0.3V.

[0119] Example 10

[0120] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that in step (5) the sodium is discharged to 2.5V.

[0121] Example 11

[0122] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that charging is performed at a current density of 5 mA / g in step (5).

[0123] Example 12

[0124] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that in step (5) the current density is 70 mA / g.

[0125] Example 13

[0126] This embodiment provides a method for electrochemical sodium replenishment, which is the same as in Example 1 except that in step (5) the sodium is charged to 3.5V.

[0127] Example 14

[0128] This embodiment provides a method for electrochemical sodium replenishment, which is the same as that in Example 1 except that charging to 5V is required in step (5).

[0129] Example 15

[0130] This embodiment provides a method for electrochemical sodium supplementation, which is the same as in Example 1 except that the activation is performed at a current density of 5 mA / g in step (5).

[0131] Example 16

[0132] This embodiment provides a method for electrochemical sodium supplementation. Except for the activation at a current density of 70 mA / g in step (5), the rest is the same as in Example 1.

[0133] Example 17

[0134] This embodiment provides a method for electrochemical sodium supplementation. Except for the activation in step (5) within the set voltage range of 1V to 4.4V, the rest is the same as in Example 1.

[0135] Example 18

[0136] This embodiment provides a method for electrochemical sodium supplementation. Except for the activation in step (5) within the set voltage range of 2V to 6V, the rest is the same as in Example 1.

[0137] Batteries containing layered sodium-ion cathode materials obtained using the electrochemical sodium supplementation method described in Examples 1-18 were tested for their first-cycle capacity versus voltage curves. The test method was as follows: charging to 4V at a constant current density of 100mA / g, then discharging to 2V at a constant current density of 100mA / g, with a 0.5h rest period between charging and discharging. The first-cycle discharge capacity is shown in Table 1. The first-cycle capacity-voltage curve of the layered sodium-ion cathode material obtained using the electrochemical sodium supplementation method described in Example 1 is shown in the figure below. Figure 7 As shown;

[0138] Batteries containing layered sodium-ion cathode materials obtained using the electrochemical sodium supplementation method described in Examples 1-18 were subjected to cycle performance tests. The test method was as follows: 50 cycles of repeated charge-discharge were performed at a current density of 100 mA / g within a voltage range of 2.0-4.4 V. The discharge specific capacity after 50 cycles is shown in Table 1. Additionally, the layered sodium-ion cathode material from Example 1 was also tested. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Layered Na of type P2 obtained after 7 days of storage in O2 and air. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 A battery was prepared using O2, and its cycle performance was tested to obtain the layered Na from Example 1. 0.75 Ni 0.2 Fe 0.4 Mn 0.4 Layered Na of type P2 obtained after storage in O2 and air for 7 days 0.75 Ni 0.2 Fe 0.4 Mn 0.4 The cycle performance of batteries prepared with O2 and layered sodium ion cathode materials is shown in the figure below. Figure 8 As shown.

[0139] Table 1

[0140]

[0141]

[0142] From Table 1, we can obtain:

[0143] (1) The batteries containing layered sodium ion cathode materials obtained in Examples 1 to 6 have high first-cycle discharge capacity and high discharge specific capacity after 50 repeated charge and discharge cycles.

[0144] (2) By comparing Examples 1 with 7 and 8, it can be seen that the discharge current density in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the discharge current density is too low, it will lead to an increase in side reactions during discharge, resulting in a decrease in capacity and a decrease in production efficiency. When the discharge current density is too high, it will lead to a decrease in the first discharge capacity and a decrease in the discharge specific capacity after 50 repeated charge and discharge cycles. This is because the shorter discharge sodium replenishment process affects the active Na + The content of the material entering the bulk phase;

[0145] (3) By comparing Examples 1 with 9 and 10, it can be seen that the first voltage obtained after discharge in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the first voltage obtained after discharge is too small, the discharge specific capacity will decrease after 50 cycles of repeated charging and discharging. This is because an excessively low discharge cutoff voltage will cause a severe phase transition, resulting in a huge loss of discharge capacity during long cycles. When the first voltage obtained after discharge is too large, the discharge capacity in the first cycle will decrease, and the discharge specific capacity will decrease after 50 cycles of repeated charging and discharging. This is because a higher cutoff voltage cannot replenish sufficient active Na in the failed material. + ;

[0146] (4) By comparing Example 1 with 11 and 12, it can be seen that the charging current density in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the charging current density is too low, it will lead to an increase in side reactions during discharge, resulting in a decrease in capacity and a decrease in production efficiency. When the charging current density is too high, it will lead to a decrease in the first discharge capacity and a decrease in the discharge specific capacity after 50 repeated charge and discharge cycles. This is because the higher the charging current density, the faster the voltage drops and the shorter the time to the termination voltage, thus the smaller the capacity.

[0147] (5) By comparing Examples 1 with 13 and 14, it can be seen that the second voltage obtained after charging in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the second voltage obtained after charging is too small, the first discharge capacity will be smaller and the discharge capacity will be smaller after 50 repeated charge and discharge cycles. This is because the charging capacity contributed by the charging process is small, resulting in a smaller discharge capacity in the following stages. When the second voltage obtained after charging is too large, the side reactions during the discharge process will increase, leading to a decrease in capacity and a decrease in production efficiency.

[0148] (6) By comparing Examples 1 with 15 and 16, it can be seen that the activation current density in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the activation current density is too small, it will lead to an increase in side reactions during discharge, resulting in a decrease in capacity and a decrease in production efficiency. When the activation current density is too large, it will lead to a smaller discharge capacity in the first cycle and a smaller discharge specific capacity after 50 cycles of repeated charging and discharging. This is because the larger the charging current density, the faster the voltage drops and the shorter the time to the termination voltage, thus the smaller the capacity.

[0149] (7) By comparing Example 1 with 17 and 18, it can be seen that the set voltage range in step (5) of the present invention will affect the performance of the battery containing layered sodium ion cathode material. When the lowest voltage in the set voltage range is too low, the first discharge capacity will be smaller and the discharge specific capacity will be smaller after 50 charge and discharge cycles. This is because the charging capacity contributed by the charging process is small, resulting in a smaller discharge capacity in the following cycles. When the highest voltage in the set voltage range is too high, the side reaction during the discharge process will increase, resulting in a decrease in capacity and a decrease in production efficiency.

[0150] (8) By comparing Example 1 and Comparative Example 1, it can be seen that the electrochemical sodium replenishment method provided by the present invention replenishes sodium in the air-depleted layered sodium ion transition metal oxide cathode material to obtain a layered sodium ion cathode material. The sodium-ion battery prepared with the layered sodium ion cathode material has a high initial capacity and excellent cycle stability. In addition, the method also has the advantages of simple technical route and low production cost.

[0151] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A method for electrochemical sodium supplementation, characterized in that, The method includes: A battery was prepared using air-defective layered sodium ion transition metal oxide cathode material as cathode material. The battery was discharged to a first voltage at a first current density, then charged to a second voltage at a second current density, and then activated at a third current density within a set voltage range to obtain the layered sodium ion cathode material. The first current density is 10~50 mA / g, the second current density is 10~50 mA / g, and the third current density is 10~50 mA / g; The first voltage is 0.5~2V, the second voltage is 4~4.4V, and the lowest voltage in the set voltage range is 1.5~2.5V, and the highest voltage is 4~5V; The activation cycle is 3 to 5 cycles; The air-defect layered sodium-ion transition metal oxide cathode material includes air-defect layered NaxTMO2, wherein TM includes any one or a combination of at least two of Ni, Fe, Mn or Co; the air-defect layered NaxTMO2 includes O3-type or P2-type layered oxides.

2. The method according to claim 1, characterized in that, The method for preparing the battery includes: A slurry is obtained by mixing a positive electrode adhesive, a conductive agent, and an air-defective layered sodium ion transition metal oxide positive electrode material. The slurry is then coated onto a current collector and rolled to obtain a positive electrode sheet. The positive electrode sheet is then combined with a negative electrode sheet, a separator, and an electrolyte to form a battery.

3. The method according to claim 2, characterized in that, The preparation of the positive electrode adhesive includes: premixing the binder and solvent in a dry environment with a dew point temperature below -40~-60℃ to obtain the positive electrode adhesive.

4. The method according to claim 3, characterized in that, The mass ratio of binder to solvent in the positive electrode adhesive solution is 1:(20~30).

5. The method according to claim 2, characterized in that, The mixing method involves stirring for 10 to 20 hours in a dry environment with a dew point temperature below -40 to -60°C.

6. The method according to claim 2, characterized in that, The mass ratio of the positive electrode adhesive, conductive agent, and air-depleted layered sodium ion transition metal oxide positive electrode material in the mixture is (20~30):(0.5~1.5):

8.

7. The method according to claim 2, characterized in that, The preparation method further includes drying the air-defective layered sodium ion transition metal oxide cathode material before mixing.

8. The method according to claim 7, characterized in that, The drying temperature is 105~150℃, and the time is 20~30h.

9. The method according to claim 2, characterized in that, The preparation method further includes drying between the coating and the rolling process.

10. The method according to claim 9, characterized in that, The compacted density after roller pressing is 1~3 g / cm³. 3 .

11. The method according to any one of claims 2-10, characterized in that, The negative electrode sheet includes sodium sheet and / or hard carbon.

12. The method according to any one of claims 2-10, characterized in that, The diaphragm includes any one or a combination of at least two of the following: glass fiber diaphragm, polyethylene, or polypropylene.

13. The method according to any one of claims 2-10, characterized in that, The electrolyte includes any one or a combination of at least two of the following: NaClO4 electrolyte, NaPF6 electrolyte, NaTFSI electrolyte, or NaFSI electrolyte.

14. A layered sodium-ion cathode material, characterized in that, The layered sodium ion transition metal oxide cathode material is obtained by the method described in any one of claims 1 to 13.

15. A battery, characterized in that, The battery comprises the layered sodium-ion transition metal oxide cathode material as described in claim 14.

Citation Information

Patent Citations

  • Sodium supplementing method for sodium-ion battery and sodium-ion battery

    CN106848453A

  • Sodium oxide composite sodium-supplementing positive electrode active material, positive electrode material, positive electrode, sodium-ion battery and sodium supplementing method for electric formation of sodium-ion battery

    CN111293289A

  • Method for repairing and recovering lithium iron phosphate positive electrode material through electrochemical lithium removal and synchronous lithium insertion

    CN116926572A

  • KR20220026284A